Sepsis Surveillance Using Adult Sepsis Events Simplified eSOFA Criteria Versus Sepsis-3 Sequential Organ Failure Assessment Criteria*. Issue 3 (March 2019) - Rhee, Chanu; Zhang, Zilu; Kadri, Sameer S.; Murphy, David J.; Martin, Greg S.; Overton, Elizabeth; Seymour, Christopher W.; Angus, Derek C.; Dantes, Raymund; Epstein, Lauren; Fram, David; Schaaf, Richard; et al.
Abstract : Objectives: Sepsis-3 defines organ dysfunction as an increase in the Sequential Organ Failure Assessment score by greater than or equal to 2 points. However, some Sequential Organ Failure Assessment score components are not routinely recorded in all hospitals' electronic health record systems, limiting its utility for wide-scale sepsis surveillance. The Centers for Disease Control and Prevention recently released the Adult Sepsis Event surveillance definition that includes simplified organ dysfunction criteria optimized for electronic health records (eSOFA). We compared eSOFA versus Sequential Organ Failure Assessment with regard to sepsis prevalence, overlap, and outcomes. Design: Retrospective cohort study. Setting: One hundred eleven U.S. hospitals in the Cerner HealthFacts dataset. Patients: Adults hospitalized in 2013-2015. Interventions: None. Measurements and Main Results: We identified clinical indicators of presumed infection (blood cultures and antibiotics) concurrent with either: 1) an increase in Sequential Organ Failure Assessment score by 2 or more points (Sepsis-3) or 2) 1 or more eSOFA criteria: vasopressor initiation, mechanical ventilation initiation, lactate greater than or equal to 2.0 mmol/L, doubling in creatinine, doubling in bilirubin to greater than or equal to 2.0 mg/dL, or greater than or equal to 50% decrease in platelet count to less than 100 cells/μL (Centers for Disease Control and Prevention Adult Sepsis Event). We compared area under the receiver operating characteristic curves for discriminating in-hospital mortality, adjusting for baseline characteristics. Of 942, 360 patients in the cohort, 57, 242 (6.1%) had sepsis by Sequential Organ Failure Assessment versus 41, 618 (4.4%) by eSOFA. Agreement between sepsis by Sequential Organ Failure Assessment and eSOFA was good (Cronbach's alpha 0.81). Baseline characteristics and infectious diagnoses were similar, but mortality was higher with eSOFA (17.1%) versus Sequential Organ Failure Assessment (14.4%; p < 0.001) as was discrimination for mortality (area under the receiver operating characteristic curve, 0.774 vs 0.759; p < 0.001). Comparisons were consistent across subgroups of age, infectious diagnoses, and comorbidities. Conclusions: The Adult Sepsis Event's eSOFA organ dysfunction criteria identify a smaller, more severely ill sepsis cohort compared with the Sequential Organ Failure Assessment score, but with good overlap and similar clinical characteristics. Adult Sepsis Events may facilitate wide-scale automated sepsis surveillance that tracks closely with the more complex Sepsis-3 criteria. Abstract : Supplemental Digital Content is available in the text.